Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Kedisiplinan Shalat Berjamaah Peserta Didik di MA Diponegoro Bandung Tulungagung - Bagus Rahmat Al Hakim; Suripto Suripto (Departement of Mathematics Education, 2024)
This research was motivated by the low awareness of students in implementing congregational prayers which was caused by several factors including lack of support from parents and the influence of peers which had a negative impact. Therefore, there is a need for a strategy in disciplining congregational prayer services. This research aims to analyze PAI teachers' strategies in improving congregational prayer, the factors that influence congregational prayer and the impact of implementing disciplinary strategies for congregational prayer. This research is a qualitative method by collecting data through observation, interviews and documentation. The results of the research are PAI teachers' strategies for improving congregational prayer discipline, namely by implementing exemplary examples, getting used to congregational prayer at school and providing advice. Factors that influence the discipline of congregational prayer are students' self-awareness, the example of parents and teachers, and the influence of peers. And the impact of the disciplinary strategy for congregational prayer is that it is hoped that students will be able to have a sense of responsibility and practice congregational prayer in their daily lives in order to avoid cruel and evil acts.